Kitaj - Livingstone, Marco; Kitaj, R. B. (London ; New York : Phaidon, 2010)
Kitaj is a complex and controversial artist who is one of the most important figural painters of the late 20th century. This monograph is the result of a close collaboration between artist and author and includes a review of Kitaj's work.
Previous ed.: 1999.
Includes bibliographical references (p. 262-264) and indexes.
Onderzoek KASK Professioneel (OFVP)
boek
Keywords: Kitaj, R. B., -- 1932-2007.